1996
DOI: 10.5511/plantbiotechnology1984.13.185
|View full text |Cite
|
Sign up to set email alerts
|

Callus Induction and Plant Regeneration from Petal Explants of Rose(Rosa hybrida).

Abstract: Rose is one of the most important floricultural crops in the world and the production of new cultivars in this plant has been a major issue for many years. Modern roses have been mainly developed through spontaneous or artificially induced bud sport1), but the recent progress of plant biotechnology provides the alternative applications such as tissue culture2, 3) and gene manipulation technologies4) for plant breeding. In our laboratory, we have investigated the use of abundant somaclonal variations induced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…However, the addition of 0.25 mg l -1 IBA was found to be more effective since it induced root elongation (Table 2). The result also indicated that plantlets root readily in medium containing lower IBA concentration as reported in several rose species (Norton and Boe, 1982;Chatani et al, 1996;Ma et al, 1996;Ara et al, 1997;Mohan and Ibrahim, 2000).…”
Section: In Vitro Rooting Of Plantletssupporting
confidence: 71%
“…However, the addition of 0.25 mg l -1 IBA was found to be more effective since it induced root elongation (Table 2). The result also indicated that plantlets root readily in medium containing lower IBA concentration as reported in several rose species (Norton and Boe, 1982;Chatani et al, 1996;Ma et al, 1996;Ara et al, 1997;Mohan and Ibrahim, 2000).…”
Section: In Vitro Rooting Of Plantletssupporting
confidence: 71%